Amplify Your Influence - Rodriguez, René (Entrepreneur) (Ascent Audio, 2022)
Apply the latest advances in neuroscience to your real-world persuasion and influence strategies for immediate results In Amplify Your Influence: Transform How You Communicate and Lead, celebrated keynote speaker, trainer, and leadership coach Rene Rodriguez delivers an eye-opening roadmap to using applied neuroscience to improve listeners' communication ability, critical thinking, cultural awareness, and leadership skills. Based in the author's proprietary AMPLIFII system and methodologies he has taught to over 100,000 participants around the world, the book offers practical tips, useful frameworks, guided practice, and simple application exercises to help listeners create new and lasting behaviors that effect change in their life and work. Amplify Your Influence shows leaders how to: - Leverage various human motivators for positive outcomes and results - Frame and communicate their ideas in a way that encourages engagement and gets an active response - Intentionally choose a communication style based on their influence objective.